Artistic Expression as Resistance in Gilman’s “The Yellow Wallpaper” - Kandel, Churamoni (Journal of Durgalaxmi, 2025)
This paper examines and explores Charlotte Perkins Gilman’s “The Yellow Wallpaper” as an intersection of artistic resistance against patriarchal oppression. It makes a study of the protagonist’s acts of writing, imagination, and visual interpretation of the wallpaper that function as forms of defiance against the systemic silencing of women. Through clandestine journal writing, the narrator subverts the authority of her husband and physician, asserting autonomy despite the confinement imposed by the restrictive “rest cure.” The wallpaper itself emerges as a powerful symbol of female entrapment and liberation, reflecting the narrator’s psychological transformation and growing resistance. This study employs the theory of resistance to explore how the subversive narrative style, characterized by first-person narration, diary format, and stream-of-consciousness, disrupts traditional literary norms and challenges the male-dominated discourse. The story portrays the protagonist’s descent into madness not merely as psychological deterioration but as a deliberate rejection of patriarchal constraints through artistic expression. Additionally, this study examines the role of imagination as a tool for transcending oppressive realities, positioning the narrator’s visions as acts of creative survival and rebellion. This paper employs a qualitative approach with an interpretive research design to analyze the story as a powerful text of artistic resistance, offering insights into how creativity becomes a means of confronting and dismantling the systems of control.